Simplified macro-model for infill masonry walls considering the out-of-plane behaviour - André Furtado (2016)
One of the main challenges in earthquake risk mitigation is the assessment of existing buildings not designed according to modern codes and the development of effective techniques to strengthen these structures. Particular attention should be given to RC frame structures with masonry infill panels, as demonstrated by their poor performance in recent earthquakes in Europe. Understanding the seismic behaviour of masonry-infilled RC frames presents one of the most difficult problems in structural engineering. Analytical tools to evaluate infill-frame interaction and the failure mechanisms need to be further studied. This research intends to develop a simplified macro-model that takes into account the out-of-plane behaviour of the infill panels and the corresponding in-plane and out-of-plane interaction when subjected to seismic loadings. Finally, a vulnerability assessment of an RC building will be performed in order to evaluate the influence of the out-of-plane consideration in the building response. Copyright (c) 2015 John Wiley & Sons, Ltd.